The Effectiveness of Motivational Psychotherapy on Social-Emotional Competencies of Students with Type 1 Diabetes - Hossein Sahebdel; Hossein Kareshki; Hossein Mehrabi (Health Technology Assessment in Action)
Background: This study aimed to investigate the effectiveness of motivational psychotherapy on the social emotional competencies of students with type 1 diabetes. Methods: The research employed a mixed-method approach. The first phase involved qualitative and deductive content analysis. During a multi-step process, an educational package was developed and validated by the researchers using written sources and guidance from psychology experts and knowledgeable professors. The quantitative phase utilized a quasi-experimental pre-test and post-test design with a control group. The study population included all secondary school students in Gonabad during 2022 - 2023. Fifty male students were randomly selected and divided into two groups of 25 (experimental and control groups). The research instrument used was the Social-Emotional Competence questionnaire by Zuo and Ji (2012). The experimental group participated in eight 90-minute sessions of motivational psychotherapy, held twice a week, while the control group received no intervention. Data analysis was performed using SPSS- 24 software and multivariate analysis of variance. Results: The findings revealed that the motivational psychotherapy program significantly increased the social-emotional competencies of the experimental group compared to the control group (P < 0.01). These results indicate that the educational package of motivational psychotherapy is an effective method for enhancing the social-emotional competencies of secondary school students with type 1 diabetes. Conclusions: This study highlights the effectiveness of motivational psychotherapy in improving social-emotional competencies in students with type 1 diabetes. The findings underscore the importance of targeted interventions in fostering emotional and social skills among this demographic.